Corporate Governance of State-Owned Enterprises : A Toolkit - World Bank Group (Washington, DC, 2014)
This Toolkit provides an overall framework with practical tools and information to help policymakers design and implement corporate governance reforms for state-owned enterprises. It covers the key elements of corporate governance, including legal and regulatory framework, state ownership arrangements, performance management systems, financial and fiscal discipline, boards of directors, transparency and disclosure, and protection of shareholders in mixed ownership companies.